STUDENTS' PERCEPTIONS OF THE EFFECTIVENESS OF ONLINE LEARNING POLICIES IN THE COVID-19 PANDEMIC - Syafril Syafril; Mohdari Mohdari; Paulus Haniko; Andi Makkulawu Panyiwi Kessi; Muhammad Fahmi; Neti Rosiana Fadilah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Since the Covid-19 Pandemic that hit many countries including Indonesia, the government has implemented a Work From Home policy that has an impact on all fields, including education. With this government policy, the world of education takes online learning. The change in the learning system from face-to-face to distance learning has changed student learning methods. The online learning method has not been tested for its effectiveness. This research uses a quantitative descriptive method where primary data is obtained from questionnaires given to student respondents from the Antasari State Islamic University, the Open University and the Indonesian Academy of Secretary and Management Citra Nusantara, all of whom are domiciled in Banjarmasin. Data collection techniques using online survey methods with questionnaires given using Google Form. This study aims to determine student perceptions of the effectiveness of online lectures during the Covid-19 pandemic. The results showed that students did not feel the effectiveness of online lectures with the various obstacles they faced in online lectures. The toughest obstacles in conducting online lectures include the lack of supporting facilities such as a stable internet network and the absence of laptop facilities which are very important in online lectures.